Reduction in the population prevalence of hepatitis C virus viraemia among people who inject drugs associated with scale‐up of direct‐acting anti‐viral therapy in community drug services: real‐world data. (5th May 2021) - Palmateer, Norah E.; McAuley, Andrew; Dillon, John F.; McDonald, Scott; Yeung, Alan; Smith, Shanley; Barclay, Stephen; Hayes, Peter; Shepherd, Samantha J.; Gunson, Rory N.; Goldberg, David J.; Hickman, Matthew; et al.
Abstract: Background and aims: There has been little empirical evidence to show the 'real‐world' impact of scaling‐up direct‐acting anti‐viral (DAA) treatment among people who inject drugs (PWID) on hepatitis C virus (HCV) viraemia at a population level. We aimed to assess the population impact of rapid DAA scale‐up to PWID delivered through community services—including drug treatment, pharmacies, needle exchanges and prisons—in the Tayside region of Scotland, compared with Greater Glasgow and Clyde (GGC) and the Rest of Scotland (RoS). Design, setting and participants: Natural experiment, evaluated using data from national biennial surveys of PWID and national clinical data. Services providing injecting equipment (2010–18) and HCV treatment clinics (2017–18) across Scotland. A total of 12 492 PWID who completed a questionnaire and provided a blood spot (tested for HCV‐antibodies and RNA); 4105 individuals who initiated HCV treatment. Intervention and comparator, measurements: The intervention was rapid DAA scale‐up among PWID, which occurred in Tayside. The comparator was GGC/RoS. Trends in HCV viraemia and uptake of HCV therapy over time; sustained viral response (SVR) rates to therapy by region and treatment setting. Findings: Uptake of HCV therapy (last year) among PWID between 2013–14 and 2017–18 increased from 15 to 43% in Tayside, 6 to 16% in GGC and 11 to 23% in RoS. Between 2010 and 2017–18, the prevalence of HCV viraemia (among antibody‐positives) declined from 73 to 44% in Tayside, 67 to 58% in GGC and 64 to 55% in RoS. The decline in viraemia was greater in Tayside [2017–18 adjusted odds ratio (aOR) = 0.47, 95% confidence interval (CI) = 0.30–0.75, P = 0.001] than elsewhere in Scotland (2017–18 aOR = 0.89, 95% CI = 0.74–1.07, P = 0.220) relative to the baseline of 2013–14 in RoS (including GGC). Per‐protocol SVR rates among PWID treated in community sites did not differ from those treated in hospital sites in Tayside (97.4 versus 100.0%, P = 0.099). Conclusions: Scale‐up of direct‐acting anti‐viral treatment among people who inject drugs can be achieved through hepatitis C virus (HCV) testing and treatment in community drug services while maintaining high sustained viral response rates and, in the Tayside region of Scotland, has led to a substantial reduction in chronic HCV in the population.